2018
DOI: 10.1037/xhp0000462
|View full text |Cite
|
Sign up to set email alerts
|

A re-examination of “bias” in human randomness perception.

Abstract: Human randomness perception is commonly described as biased. This is because when generating random sequences humans tend to systematically under- and overrepresent certain subsequences relative to the number expected from an unbiased random process. In a purely theoretical analysis we have previously suggested that common misperceptions of randomness may actually reflect genuine aspects of the statistical environment, once cognitive constraints are taken into account which impact on how that environment is ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 40 publications
(79 reference statements)
0
38
0
Order By: Relevance
“…Therefore, their prediction errors cannot be completely removed. Misperception of randomness can be due to cognitive biases or not [5], but it does exist. Flipping a coin, the chance of heads three times in a row is 1 1 1 1 0.125 2 2 2 8 × × = = .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, their prediction errors cannot be completely removed. Misperception of randomness can be due to cognitive biases or not [5], but it does exist. Flipping a coin, the chance of heads three times in a row is 1 1 1 1 0.125 2 2 2 8 × × = = .…”
Section: Discussionmentioning
confidence: 99%
“…Inherent bias prevents total randomness. Completely unbiased random changes in a sustainable complex system are impossible, by virtue of constraints imposed by the intrinsic organization in the system (Warren et al, 2018). Models of kinetic reaction-diffusion equations are used to describe microscopic biological populations dynamics (Cordier, 2016).…”
Section: Randomness In Biologymentioning
confidence: 99%
“…In addition, common misperceptions of randomness reflect genuine aspects of the statistical environment. When cognitive constraints are taken into account they impact how that environment is experienced [108]. When people consider a series of random binary events, such as flipping a coin, they tend to erroneously underrate the probability of sequences with less internal structure [109].…”
Section: Introductionmentioning
confidence: 99%
“…Comparing human-generated sequences to unbiased process-generated binary sequences demonstrated that the constraints imposed on human experience provide a more meaningful picture of our ability to perceive randomness. A model of human random-sequence generation was thus proposed [108]. Binary sequences consist of a mixture of alternation and repetition.…”
Section: Introductionmentioning
confidence: 99%